Adaptive associations among life history, reproductive traits, environment, and origin in the Wisconsin angiosperm flora. Issue 12 (14th December 2020) - Givnish, Thomas J.; Kriebel, Ricardo; Zaborsky, John G.; Rose, Jeffrey P.; Spalink, Daniel; Waller, Donald M.; Cameron, Kenneth M.; Sytsma, Kenneth J.
Abstract : Premise: We tested 25 classic and novel hypotheses regarding trait–origin, trait–trait, and trait–environment relationships to account for flora‐wide variation in life history, habit, and especially reproductive traits using a plastid DNA phylogeny of most native (96.6%, or 1494/1547 species) and introduced (87.5%, or 690/789 species) angiosperms in Wisconsin, USA. Methods: We assembled data on life history, habit, flowering, dispersal, mating system, and occurrence across open/closed/mixed habitats across species in the state phylogeny. We used phylogenetically structured analyses to assess the strength and statistical significance of associations predicted by our models. Results: Introduced species are more likely to be annual herbs, occupy open habitats, have large, visually conspicuous, hermaphroditic flowers, and bear passively dispersed seeds. Among native species, hermaphroditism is associated with larger, more conspicuous flowers; monoecy is associated with small, inconspicuous flowers and passive seed dispersal; and dioecy is associated with small, inconspicuous flowers and fleshy fruits. Larger flowers with more conspicuous colors are more common in open habitats, and in understory species flowering under open (spring) canopies; fleshy fruits are more common in closed habitats. Wind pollination may help favor dioecy in open habitats. Conclusions: These findings support predictions regarding how breeding systems depend on flower size, flower color, and fruit type, and how those traits depend on habitat. This study is the first to combine flora‐wide phylogenies with complete trait databases and phylogenetically structured analyses to provide powerful tests of evolutionary hypotheses about reproductive traits and their variation with geographic source, each other, and environmental conditions.